(Hetero)arylboration of alkynes: a strategy for the synthesis of α, α-bis(hetero)arylketones. Issue 24 (5th June 2019) - Huang, Yuan; Bergmann, Allison M.; Brown, M. Kevin
Abstract : A method for (hetero)arylboration of alkynes is presented. Abstract : A method for (hetero)arylboration of alkynes is presented. The reaction allows for the synthesis of densely functionalized tetrasubstituted alkenes with control of regioselectivity and diastereoselectivity. The conversion of the products to the corresponding α, α-bis(hetero)arylketones is also shown.